Analisis Faktor- Faktor Yang Mempengaruhi Pembelian Green Pada Mahasiswa Daerah Istimewa Yogyakarta - Ascasaputra Aditya; Jumadi; Retno Septiana (Jurnal Ilmiah Neraca : Ekonomi Bisnis, Manajemen, Akuntansi, 2025)
Green marketing is one of the activities carried out by companies to apply concepts that pay attention to the environment in marketing activities. Several studies regarding the factors that cause the purchase of green products have produced different findings. There are several factors that influence the purchase of green products, including: perceived product price & quality (PQ), organization's green image (OGI), environmental concern (EC), and environmental knowledge (EK) on green purchase intention (GPI). Other research finds that perceived green value, perceived consumer effectiveness and environmental knowledge. To find out in more detail about the factors that influence green purchases, researchers conducted a descriptive analysis of indicators from the Environmental concern variable (Channa et al., (2021), Green product (Emekei, 2019), Perceived price (Lavuri & Susandy, 2020) , and Green buying behavior (Ghali-Zinoubi, 2020). The results obtained were that respondents paid the most attention to environmentally friendly product labels and content information on products. Apart from that, researchers also obtained data about green products that were often purchased, namely bags and eating and drinking utensils, apart from this. It was found that green products were purchased more offline in retail stores than online. keyword: Product green, Perceived price, Environmental concern, Green buying behaviour